MARX AND THE PROBLEM OF LACK OF WORK - Dimarco, Sabina (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
Based on a number of studies that have been analyzed from a socio-historical perspective the process of social construction of unemployed, the article analyzes the way in which the lack of work in valid people is problematized in Karl Marx's works. The paper posed that Marx’s reflections in this issue provides elements that will be essential for the further shaping of such social category. This article constitutes an introduction to the question of the role played by the first Marxists in Argentina in introducing a new perspective for interpretation of the lack of work, forged in dialogue with Marxist ideas circulating in an international context but also in dispute with the perceptions of this period.